PENGARUH INDEPENDENSI, KOMPETENSI DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT: ETIKA SEBAGAI VARIABEL MODERASI - Maharani Maharani; Rina Trisnawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Auditors are required to be able to carry out a quality audit. Several factors need to be considered by auditors related to independence, competence, accountability and ethics. Purpose of the study are determined and analyzed the effect of independence, competence, and accountability on audit quality with auditor ethics as a moderating variable. This research includes descriptive research using a survey approach. The research population is all auditors who work at KAP in Surakarta and DIY. Samples were taken as many as 33 auditors in KAP Surakarta and DIY. The sampling technique used was convenience sampling. Data collection techniques using a questionnaire. The data analysis technique used classical assumption test and multiple regression analysis, t test, F test, and coefficient of determination test. The results of the study show that: (1) Independence, competence, and accountability partially have a significant effect on audit quality; (2) The interaction between auditor independence and ethics has a significant effect on audit quality; (3) The interaction between the competence and ethics of auditors has a significant effect on audit quality; (4) The interaction between accountability and auditor ethics has a significant effect on audit quality. This means that auditor ethics is a moderating variable that affects the relationship between independence, competence, and accountability with audit quality.